2021
DOI: 10.1016/j.immuni.2021.10.015
|View full text |Cite
|
Sign up to set email alerts
|

A non-classical monocyte-derived macrophage subset provides a splenic replication niche for intracellular Salmonella

Abstract: Summary Interactions between intracellular bacteria and mononuclear phagocytes give rise to diverse cellular phenotypes that may determine the outcome of infection. Recent advances in single-cell RNA sequencing (scRNA-seq) have identified multiple subsets within the mononuclear population, but implications to their function during infection are limited. Here, we surveyed the mononuclear niche of intracellular Salmonella Typhimurium ( S .Tm) during early … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…Yet these crucial immune cells can also act as a cellular niche and form granulomas, which are immunological structures that function as a host mechanism to contain infection but within which intracellular bacteria are able to survive. Understanding of macrophage functional diversity requires delineation not only of macrophages within granulomas but also precursor cells that give rise to these and other macrophages in the infected tissue environment (32,35,37,57).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet these crucial immune cells can also act as a cellular niche and form granulomas, which are immunological structures that function as a host mechanism to contain infection but within which intracellular bacteria are able to survive. Understanding of macrophage functional diversity requires delineation not only of macrophages within granulomas but also precursor cells that give rise to these and other macrophages in the infected tissue environment (32,35,37,57).…”
Section: Discussionmentioning
confidence: 99%
“…Yet these crucial immune cells can also act as a cellular niche and form granulomas, which are immunological structures that function as a host mechanism to contain infection but within which intracellular bacteria are able to survive. Understanding of macrophage functional diversity requires delineation not only of macrophages within granulomas but also precursor cells that give rise to these and other macrophages in the infected tissue environment(32, 35, 37, 57). Here, we apply single-cell transcriptomics to investigate macrophage heterogeneity in S Tm-infected spleens to gain insight into how their heterogeneity and functional diversity contribute to controlling bacterial persistence and infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their ability to restrict intracellular bacilli, alveolar MΦs were shown to exhibit M2-like characteristics and thereby served as a more favorable replicative niche for Mtb . In a recent single-cell RNA sequencing (scRNA-seq) study of acute S Tm infection in mice for 48 hours after inoculation, when granulomas are yet to form and bacterial levels are uncontrolled, a non–classical monocyte (CM)–derived MΦ population was found to harbor more intracellular bacilli than other mononuclear phagocytes (MNPs) ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the host side, macrophages infected with S .Tm generates well-documented heterogeneous phenotypes during intracellular infection (Burton et al, 2014). Recent single cell RNA-seq (scRNA-seq) studies revealed host signatures of macrophage subpopulations that display diverse outcomes: some are permissive to intracellular bacterial growth (Hoffman et al, 2021); some will lyse the ingested bacteria (Huang et al, 2018); others allow bacteria to persist intracellularly (Stapels et al, 2018). But scRNA-seq methods are limited to profiling only host transcripts as they rely on polyA priming of mRNAs, while bacterial mRNAs lack polyA.…”
Section: Introductionmentioning
confidence: 99%